UPAYA MENINGKATKAN AKTIVITAS BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA PADA MATERI BANGUN RUANG MELALUI STRATEGI PEMBELAJARAN KONTEKSTUAL DI KELAS VIII SMP MUHAMMADIYAH 02 KECAMATAN MEDAN PERJUANGAN TAHUN PELAJARAN 2014/2015 - Syahriani Nasution (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
This study aims to determine the increased activity of learningmathematics and communication skills of students by implementingcontextual learning strategy on material geometry flat side. Resultsobservation student activity is still relatively low, the percentage ofstudents who take the activity of learning activities by 45%. The testresults obtained by students' communication skills math average valueof 21.56 and classical completeness 34%. After applying contextuallearning strategies acquired percentage of student activity by 58% andmathematical communication skills of students in the first cycle obtainthe percentage of classical completeness 51% and the average value of24.49. In the second cycle, the percentage of student activity wasobtained at 78% and mathematical communication skills studentsacquired classical completeness of 88%. It can be concluded that thereis increased activity of learning mathematics and communication skillsof students by implementing contextual learning strategies.